Austria : 2016 Article IV Consultation-Press Release; and Staff Report for Austria. (IMF Staff Country Reports; Country Report ;, 2017)
This 2016 Article IV Consultation highlights that the economic recovery in Austria has strengthened in 2016. GDP growth in 2016 is estimated at 1.4 percent, an improvement over the average growth of 0.6 percent in 2012-15. Growth has been broad-based, driven by private consumption supported by income tax cuts, a recovery in investment, and higher public consumption owing to spending on refugees. Employment growth has picked up as well. The outlook for 2017 appears similarly robust, while in the medium term growth would decline toward its potential rate, which IMF staff estimate at slightly higher than 1 percent. Risks to the outlook are mainly external, with limited likely impact overall.